Patients' experiences of day surgery and recovery: A meta‐ethnography - Cathrine Ween Thoen; Monica Sæle; Ragnhild Bjarkøy Strandberg; Petrin Hege Eide; Liv Grethe Kinn (Wiley, 2024)
Abstract Aim To explore and synthesise findings from qualitative studies on adult patients' experiences of day surgery and the processes of recovery. Background There has been a shift in the practice of elective surgery, from inpatient to ambulatory treatment. Accordingly, more patients are undergoing day surgery and expected to care for themselves at home. To our knowledge, an updated metasynthesis on patients' experiences of day surgery across diverse contexts and continents is lacking. Design Meta‐ethnography. Methods MEDLINE, EMBASE and CINAHL were systematically searched for qualitative research in English published between 2006 and 2023. Noblit and Hare's meta‐ethnographic approach guided the synthesis of findings from 12 qualitative studies, and the eMERGe Reporting Guidance was used in the writing of this article. Results Four themes were revealed: (1) requests for tailored information, (2) challenges of recognising and understanding postoperative symptoms, (3) being dependent on continuous professional and personal support and (4) calling for individual adaptation. Conclusion Our meta‐ethnography indicates there is a need to improve information provision to better prepare patients for the processes of day surgery and recovery and promote their self‐care abilities. Our findings highlight the importance of ensuring adequate levels of individualised care and support throughout the treatment process. Relevance to Clinical Practice To improve quality of care in day surgery practice, implementation of interventions to enhance information provision and promote self‐care during recovery at home may be considered. Pre‐admission appointments that incorporate provision of tailored information and assessment of the patients' individual needs of care and support, home conditions and access to assistance from family/friends can be recommended.